Peningkatan Kreativitas Karang Taruna Melalui Pelatihan Desain Grafis dan Konten Digital - Ahmad Faqih; Ahmad Rifai; Mohamad Riad Solihin; Muhammad Daffa Ayyasy (CV. Multi Kreasi Media, 2022)
The role of youth in village development is becoming increasingly important in the digital era, particularly in promoting local potential, social activities, and creative economic initiatives. One of the main challenges faced by youth organizations such as Karang Taruna is the limited ability to produce engaging digital content and graphic designs, despite the great potential of social media as a means of promotion and communication. This Community Service Program (PKM) aims to enhance the capacity of Karang Taruna members in creating creative content and graphic design using simple and accessible digital applications. The program was carried out in several stages: identifying participants’ needs, developing training modules, conducting in-person training sessions, and providing post-training assistance. The training materials included the basics of graphic design, understanding visual elements (color, typography, layout), simple photography and videography techniques using smartphones, and the use of design applications such as Canva, CapCut, and Pixellab. Participants also practiced creating social media content to promote village activities, local MSMEs, and social campaigns managed by Karang Taruna. The results show a significant improvement in participants' skills in designing posters, Instagram feeds, and short videos for publication purposes. Some of the participants' works have been uploaded to Karang Taruna’s official social media accounts and received positive responses from the community. This program not only enhanced technical skills but also fostered confidence, creativity, and a spirit of collaboration among members. It makes a tangible contribution to empowering village youth through digital literacy and creative media. Moving forward, this training can be developed into a sustainable program to strengthen the village’s digital identity and promote local potential through community-based efforts.